2013
DOI: 10.3389/fnbeh.2013.00131
|View full text |Cite
|
Sign up to set email alerts
|

An Error-Related Negativity Potential Investigation of Response Monitoring Function in Individuals with Internet Addiction Disorder

Abstract: Internet addiction disorder (IAD) is an impulse disorder or at least related to impulse control disorder. Deficits in executive functioning, including response monitoring, have been proposed as a hallmark feature of impulse control disorders. The error-related negativity (ERN) reflects individual’s ability to monitor behavior. Since IAD belongs to a compulsive-impulsive spectrum disorder, theoretically, it should present response monitoring functional deficit characteristics of some disorders, such as substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…Regarding the reflective system, the most convincing results are twofold: On the one hand control monitoring difficulties, as evidenced by ERN impairments both in excessive online computer gamers (Littel et al, 2012) and in a sample of IA including the different kinds of associated behaviors (Zhou et al, 2013). On the other hand, the reduction in delta and beta power resting-state waves of excessive online computer gamers (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the reflective system, the most convincing results are twofold: On the one hand control monitoring difficulties, as evidenced by ERN impairments both in excessive online computer gamers (Littel et al, 2012) and in a sample of IA including the different kinds of associated behaviors (Zhou et al, 2013). On the other hand, the reduction in delta and beta power resting-state waves of excessive online computer gamers (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Higher impulsivity and error rates for NoGo trials were also reported, these measures being correlated with ERN alterations. Recently, these findings have been extended to a A C C E P T E D M A N U S C R I P T (Brard and Wolf, 2001)], and that was controlled for comorbid neurological, psychiatric and other addictive disorders (Zhou et al, 2013). As compared to the 23 controls, IA showed faster RTs but lower accuracy and reduced ERN amplitude in a modified Eriksen Flanker task (requiring to detect the direction of a central arrow while ignoring incongruent flankers).…”
Section: Reflective Systemmentioning
confidence: 96%
“…In fact, the 'mere' perception of some veil of anonymity, or of some digital shield, and however false, appears to promote disinhibition [209]. Adjacently, it has been noted that, "[a] hallmark personality characteristic in substance abuse is impulsivity, and impulsivity is related to increased sensitivity to reward and decreased sensitivity to punishment" [210]. Zhou and Li have recorded that "[w]ithin neuropsychology and cognitive neuroscience, impulsivity is often equated with the term "disinhibition," and that "…inhibitory control mechanisms may be disrupted … resulting in a predisposition toward impulsive acts."…”
Section: Psychosocial Characterizations Of the Digital Workforces In mentioning
confidence: 99%
“…Alterations in cognitive flexibility in this model are seen even in an undrugged state in sensitized animals, strongly corroborating the face validity of this particular model of OCD, especially for cognition studies. A relatively novel phenomenon is Internet addiction, which is the topic of another article by Zhou et al (2013), who examine error-related negativity potentials in Internet-addicted subjects. Two preclinical papers from the field of epileptology (both by Mikulecká et al, 2014a,b) report delayed negative consequences of the postnatal administration of clonazepam on cognitive and social behaviors.…”
mentioning
confidence: 99%
“…A report by Hatalova et al (2014) uses an animal model of OCD based on sensitization by quinpirole, a D2-like receptor agonist, and suggests evidence for disrupted cognitive flexibility tested in spatial memory, cognitive co-ordination, and flexibility tasks. Evidence of cognitive flexibility in OCD in Zhou et al (2013), who examine error-related negativity potentials in Internet-addicted subjects. Two preclinical papers from the field of epileptology (both by Mikulecká et al, 2014a,b) report delayed negative consequences of the postnatal administration of clonazepam on cognitive and social behaviors.…”
mentioning
confidence: 99%